Personality predictors of 6‐month readmission in adult psychiatric inpatients. (8th March 2022) - Cruess, Dean G.; Sullivan, Matthew C.; Strainge, Lauren; Blackmon, Jaime E.; Laumann, Laura; Wheeler, David; Cruess, Stacy E.
Abstract : Readmission of psychiatric inpatients is highly prevalent and places a significant financial burden on the healthcare system. Rehospitalisation is often used as a metric of quality of care in psychiatric settings, but little is known about how specific personality traits impact readmission in adult psychiatric inpatients. A convenience sample of 94 adults (mean age = 36.8 years; female = 54.3%; European American = 76.6%) at an inpatient psychiatric hospital completed the Personality Inventory for DSM‐5‐Brief Form (PID‐5‐BF; American Psychiatric Association, 2013); demographic and medical information and readmission data were extracted via chart review. Poisson regression was used to predict number of readmissions at 6 months after discharge from PID‐5‐BF domain scores of Negative Affectivity, Detachment, Antagonism, Disinhibition and Psychoticism. Twenty‐three patients (24.5%) were readmitted at least once by 6‐month follow‐up. Higher PID‐5‐BF Negative Affectivity domain scores predicted greater number of readmissions at 6 months (incidence rate ratio (IRR) = 1.14, robust standard error (RSE) = 0.05, p < .01, 95% confidence interval [1.04, 1.25]). The other PID‐5‐BF domain scores were not significantly related to number of readmissions. Thus, greater negative affect, indicative of higher trait neuroticism, heightened experience of negative emotions and poor self‐concept, was a significant personality predictor of readmission in the study. These results suggest that assessing this trait domain might help to identify psychiatric inpatients at greater risk for readmission and determine those most in need of enhanced services to reduce rehospitalisation.